Da Lei Bosman ao sportswashing: a racionalidade neoliberal no futebol global - Carvalho, Renan Augusto (2024)
This article investigates the relationship between globalization, neoliberalism, and contemporary football, analyzing how these forces have transformed the sport into a transnational phenomenon that reflects and reproduces the inequalities and contradictions of modern capitalism. Drawing on a theoretical approach that considers neoliberal rationality as a pervasive logic permeating various spheres of social life, the study explores the economic, political, and cultural impacts of this rationality on global football. To this end, two emblematic cases are analyzed: the Bosman law and the practice of sportswashing by European clubs such as Manchester City, Newcastle United, and Paris Saint-Germain. Through these cases, the article demonstrates how neoliberalism reconfigures power dynamics, subjectivation, and governmentality in the sport, turning players into commodities and instrumentalizing football for geopolitical purposes. The conclusion is that neoliberal rationality, by penetrating football, not only redefines social and cultural practices but also presents challenges for resistance and the maintenance of local and community ties. Submission: Ago 15, 2024 ⊶ Accepted: Nov 09, 2024